Symmetrically Substituted Zn and Al Phthalocyanines and Polymers for Photodynamic Therapy Application - Prabhu C. P., Keshavananda; Nemakal, Manjunatha; Managa, Muthumuni; Nyokong, Tebello; Koodlur Sannegowda, Lokesh (Frontiers in Chemistry, 2021)
N4 macrocyclic complexes of Al and Zn phthalocyanines with symmetrical imine and imidazole moiety at the periphery were synthesized. The synthesized ligands, complexes and polymers were purified and characterized to study the structure of the molecule. These synthesized complexes were used for photodynamic therapy (PDT) application as the diamagnetic Zn and Al have the ability to produce and stabilize singlet oxygen species. The synthesized N4 molecules of aluminium imino methoxy phenyl phthalocyanine and aluminium ethyl phenyl benzimidazole phthalocyanine showed better activity against MCF-7 cell. These results suggest that this assay may be used as an early biomarker of clinical response.